The Check and Report Ebola (CARE+) Program to Monitor Travelers for Ebola After Arrival to the United States, 2014-2016. (November 2019) - Joseph, Heather A.; Wojno, Abbey E.; Winter, Kelly; Grady-Erickson, Onalee; Hawes, Erin; Benenson, Gabrielle A.; Lee, Amanda; Cetron, Martin
The 2014-2016 Ebola epidemic in West Africa influenced how public health officials considered migration and emerging infectious diseases. Responding to the public's concerns, the US government introduced enhanced entry screening and post-arrival monitoring by public health authorities to reduce the risk of importation and domestic transmission of Ebola while continuing to allow travel from West Africa. This case study describes a new initiative, the Check and Report Ebola (CARE+) program that engaged travelers arriving to the United States from countries with Ebola outbreaks. The Centers for Disease Control and Prevention employed CARE ambassadors, who quickly communicated with incoming travelers and gave them practical resources to boost their participation in monitoring for Ebola. The program aimed to increase travelers' knowledge of Ebola symptoms and how to seek medical care safely, increase travelers' awareness of monitoring requirements, reduce barriers to monitoring, and increase trust in the US public health system. This program could be adapted for use in future outbreaks that involve the potential importation of disease and require the education and active engagement of travelers to participate in post-arrival monitoring.